Free minimal resolutions and the Betti numbers of the suspension of an n-gon - Tilak de Alwis (International Journal of Mathematics and Mathematical Sciences)
Consider the general n-gon with vertices at the points 1,2,…,n. Then its suspension involves two more vertices, say at n+1 and n+2. Let R be the polynomial ring k[x1,x2,…,xn], where k is any field. Then we can associate an ideal I to our suspension in the Stanley-Reisner sense. In this paper, we find a free minimal resolution and the Betti numbers of the R-module R/I.